Comparative proteomic analysis of malignant pleural mesothelioma evidences an altered expression of nuclear lamin and filament‐related proteins. Issue 3 (12th February 2014) - Giusti, Laura; Da Valle, Ylenia; Bonotti, Alessandra; Donadio, Elena; Ciregia, Federica; Ventroni, Tiziana; Foddis, Rudy; Giannaccini, Gino; Guglielmi, Giovanni; Cristaudo, Alfonso; Lucacchini, Antonio; Semba, Richard D.; et al.
<x xml:space="preserve">Abstract</x> Purpose Malignant mesothelioma is a neoplastic disease linked to asbestos exposure whose diagnosis is limited, so detection methods for an early diagnosis and treatment result essential. Here, we compared proteomic profiles of malignant pleural mesothelioma (MPM) and benign biopsies to search potential biomarkers useful in differential diagnosis. Experimental design Tissue biopsies were obtained from 53 patients who were subjected to a diagnostic thoracoscopy. 2DE/MS based approach was used for proteomic analysis and protein validation was carried out by Western blot analysis versus benign and lung carcinoma samples. Results Among the proteins identified we confirmed known MPM biomarkers such as calretinin and suggested the new ones as prelamin A/C, desmin, vimentin, calretinin, fructose‐bisphosphate aldolase A, myosin regulatory light chain 2, ventricular/cardiac muscle isoform, myosin light chain 3 and myosin light chain 6B. Ingenuity software was used to identify the biological processes to which these proteins belong and to construct a potential network. Conclusions and clinical relevance Overall, our results suggest potential biomarkers that can be useful in occupational medicine for the early identification of the onset of disease in health surveillance of past asbestos‐exposed workers, for monitoring the progress of disease and for assessing the response to treatment.